A hill of light is sadly dimmed - Abd Razak, Dzulkifli (2005)
CAHAYA in English means, "light". The light over a hill called Bukit Cahaya near Seri Alam Agriculture Park, somehow has been dimmed. What was a lush 886ha area of beautiful piece of natural vegetation suddenly turned barren and ugly. Some argue that this is fated since Bukit Cahaya is another name for Bukit Cerakah, the former being popularised for fear that the latter could be mis pronounced as Bukit Celaka. Ironically, celaka which literally means "grave misfortune", now seems more fitting to describe what is left of Bukit Cahaya as a result of utter carelessness. Sources from the Ministry of Agriculture and Agrobased Industries estimated that the park had suffered a RM4.2million environmental carnage, making it prone to flooding in certain areas. For example, as late as November 2003, there was reportedly a flash flood with water rising up to eight metres, believed to be related to the so called development around its vicinity.